Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
The given quadratic equation is expressed as
2x^2 - 3x - 1 = 0
We would apply the general formula for quadratic equations which is expressed as
[tex]\begin{gathered} x\text{ = }\frac{-b\text{ +/-}\sqrt{b^2-4ac}}{2a} \\ \text{Looking at the equation,} \\ a\text{ = 2, b = - 3 and c = - 1} \\ \text{If we substitute these values into the formula, it becomes} \\ x\text{ = }\frac{--3\text{ +/-}\sqrt{-3^2-4(2\times-1}}{2\times-1} \\ x\text{ = }\frac{3\text{ +/-}\sqrt{9+8}}{-2} \\ x\text{ = }\frac{3\text{ +/-}\sqrt{17}}{-2} \\ x\text{ = }\frac{3\text{ + }\sqrt{17}}{-\text{ 2}}\text{ or }\frac{3\text{ - }\sqrt{17}}{-\text{ 2}} \\ x\text{ = }\frac{3\text{ + 4.12}}{-\text{ 2}}\text{ or }\frac{3\text{ - 4.12}}{-2} \\ x\text{ = - 3.56 or x = 0.56} \end{gathered}[/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.